Piloting Wet Tensile Strength Development of Polyamide-Amine-Epichlorohydrin Wet Strengthened Nordic Bleached Softwood Pulp Paper by Alkyl Ketene Dimer Internal Sizing - Antti Korpela; Aayush Kumar Jaiswal; Atsushi Tanaka; Jaakko Asikainen (BioResources, 2022)
The results of recent laboratory-scale studies regarding the joint effects of wet strengthening agent polyamide-amine-epichlorohydrin (PAE) and internal alkylketene dimer (AKD) sizing on Nordic bleached softwood pulp (NBSK) handsheets indicate that AKD internal sizing increases the wet strength of PAE wet strengthened handsheets. The boosting effect of the internal AKD sizing was long-lasting. At the molecular level the actual mechanism behind the effect is unclear. The present study examines if the enhanced effect of internal AKD sizing, which is potentially exploitable in practice, also occurs in paper made by VTT’s Suora pilot paper machine. The trials were done using a similar type of NBSK pulp and the same chemicals as in the laboratory-scale studies. The paper was formed at 400 m/min using a hybrid dewatering mode (Fourdrinier + gap). Just as in the laboratory-scale studies, the internal AKD sizing of PAE wet-strengthened NBSK paper resulted in a long-lasting increase of the paper wet strength. In accordance with the laboratory trials, internal AKD sizing had no noticeable effect on the dry tensile strength of the pilot-made paper. The only apparent difference to the earlier observations was an increase of dry tensile strength of the paper treated solely with PAE.